2015
DOI: 10.3748/wjg.v21.i8.2269
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis C virus infection and neurological and psychiatric disorders: An overview

Abstract: Hepatitis C virus (HCV) infection is considered a systemic disease because of involvement of other organs and tissues concomitantly with liver disease. Among the extrahepatic manifestations, neuropsychiatric disorders have been reported in up to 50% of chronic HCV infected patients. Both the central and peripheral nervous system may be involved with a wide variety of clinical manifestations. Main HCV-associated neurological conditions include cerebrovascular events, encephalopathy, myelitis, encephalomyelitis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
157
0
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(175 citation statements)
references
References 141 publications
2
157
0
16
Order By: Relevance
“…HCV has been proposed to prompt demyelination via an immunemediated response. These findings proposed that in cases with acute disseminated encephalomyelitis the likelihood of HCV infection in creases [11] .…”
Section: Cns Involvement In Hcv Infectionmentioning
confidence: 96%
See 1 more Smart Citation
“…HCV has been proposed to prompt demyelination via an immunemediated response. These findings proposed that in cases with acute disseminated encephalomyelitis the likelihood of HCV infection in creases [11] .…”
Section: Cns Involvement In Hcv Infectionmentioning
confidence: 96%
“…It is reported that chronic HCV infection has been associated with neurological as well as psychiatric conditions in upto about 50% of the cases [11] . Major HCV related neurological ailments comprise of autoimmune disorders, cerebrovascular events, myelitis, encephalopathy, encephalomyelitis, and cognitive impair ment; psychiatric disorders include, anxiety depression, and fatigue [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor NF-ÎșB is reported to be involved in cytokine gene expression. Therefore, blocking NF-ÎșB can be a therapeutic approach to controlling HCV mediated neuroinflammation [52] . According to the above study, viral core proteins have been observed to activate microglial cells, astrocytes, and macrophages of patients infected with HCV.…”
Section: Increased Hepatitis C Virus Replication and Neurotoxicity Wimentioning
confidence: 99%
“…Along with the increased risk of vascular disease in HCV positive patients, evidence has also shown an increased cardiovascular mortality risk [57,58]. Finally, the mechanism of the neuropsychiatric manifestation (depression and brain fog) of HCV may be related to the virus invading both the white brain matter and brain stem, as well as the impact of circulating HCV-related cytokines on the brain [59][60][61][62][63]. Furthermore, the cause of chronic fatigue (both peripheral and central fatigue) observed during HCV infection is unknown but is also thought to be a result of the disruption in cellular activity caused by the effects of circulating inflammatory cytokines and chemokines [60,62].…”
Section: Hcv and Its Treatmentmentioning
confidence: 99%